The mechanical performance of ARB fabricated hybrid lamellar composite of recovered/recrystallized Al and precipitation hardened Al(Sc) layers - Quadir, Md Zakaria; Al-Buhamad, O.; Ferry, M. (2011)
Sheets of commercial purity aluminum and super saturated solid solution of 0.3% Sc were accumulatively roll bonded to form 64 alternating layers in a 0.5 mm thickness. The rolling was done at 350 °C to ensure dynamic recovery/recrystallization in Al layers and precipitation hardening of Al(Sc) layers during the rolling. The sheet crystallographic texture was distributed along ß fibre orientations. The recrystallization texture of aluminum layers after annealed at 250-350 °C was randomly distributed. The tensile property of this novel composite has achieved a small improvement over the commercially available grades and delamination between the layers was identified as the key issue to improve in this fabrication technique.